Prediction of Beam Stiffness for Structural Glued laminated Timber - Ong, Chee Beng (2004)
The objective of the study was made to develop a probabilistic model for predicting the statistical distribution of stiffness properties of some selected Malaysian timbers.In this respect, a three-step experimental approach was adopted before simulated beam stiffness for the species population was derived. Firstly, a number of probability functions representing the actual distribution of selected timber data were examined. Goodness-offit (GOF) analysis was then carried out to establish the best fitting distribution function for the experimental data used.Secondly, the modulus of elasticity (MOE) of solid and finger-jointed samples was obtained from non-destructive testing (NDT) using the fundamental vibration frequency methodology. Results from the above method were calibrated against those obtained through static bending test by means of Universal Testing Machine. Finally, glued-laminated timber (glulam) beams were fabricated using laminations with predetermined MOEs by NDT method and the beams were later subjected to 3-point static bending test for MOE determination.In the mean time, finite element method (FEM) coupled with transformed section approach, was also used to simulate the glulam beam tests after experimental length effect was incorporated.The MOE of beams population was then predicted using randomly generated MOE and length data.The GOF analysis indicates that 3-parameter Weibull distribution best fit the probability distribution of the tested timber. Results from the NDT method also showed a good relationship between the fundamental vibration frequency test and the static bending test conducted with a coefficient of determination of about 0.89. In the simulation of glulam beams, the MOE values of simulated glulam beams are generally higher than the actual tests conducted, particularly in durian hutan, with a percentage difference of about 23%.In the prediction of the MOE glulam beams population, the generated distribution exhibits higher MOE values compared to the average value reported respectively for durian hutan and rubberwood species